Betalains protect various body organs through antioxidant and anti-inflammatory pathways - Nilesh Prakash Nirmal; Seema Medhe; Merina Dahal; Pankaj Koirala; Siriwan Nirmal; Fahad Al-Asmari; Baojun Xu (Food Science and Human Wellness)
Betalains are natural coloring pigments with betalamic acid as the core structure of all subclasses. Besides their coloring properties, betalains exhibit various biological activities, including antioxidant and anti-inflammatory properties, which are highly imperative. Further in-vivo studies reported that betalains protect various body organs, leading to health enhancement. Body organs, including the heart, liver, kidney, lung, etc., are important for a healthy life. However, these organs can be affected or damaged by various stress factors, toxicants, and harmful substances. Recent studies have claimed that betalains could protect all vital organs of the body through antioxidant and anti-inflammatory mechanisms. This review article described the in-vivo antioxidant and anti-inflammatory activities of betalains in various cell-line or animal models. A comprehensive discussion has been provided on the mechanism of action of betalains in protecting various body organs, including cardio-protective effect, hepato-protective ability, renal protection capacity, repro-protective ability, neuro-protective effect, lung protection, and gut protection ability. Finally, future research directions and conclusions have been outlined.